Pharmacological Inhibition of Hsp70 to Degrade c-FLIP: A Novel Indirect Approach for Cancer Therapy: A Narrative Review - Jumaa, Azal Hamoody; Al-Tameemi, Sadeq Jaafer; Sabah, Muthanna Atia; Yasin, Youssef Shakuri (Kurdistan Journal of Applied Research, 2026)
The cellular FLICE-inhibitory protein (c-FLIP) is a master regulator of pro-grammed cell death, functioning as a key suppressor of extrinsic apoptosis mediated by death receptor signaling. Its persistent overexpression is a hall-mark of numerous cancers, contributing directly to tumorigenesis, therapy resistance, and immune evasion. However, direct pharmacological targeting of c-FLIP has proven exceptionally challenging because of its unstructured protein-interaction domains. This review explores an innovative indirect strategy: inhibiting the molecular chaperone heat shock protein 70 (Hsp70) to promote the proteasomal degradation of c-FLIP. Hsp70 is frequently overex-pressed in malignancies and is critically involved in stabilizing oncoproteins, such as c-FLIP, shielding them from ubiquitination and degradation. A syn-thesis of compelling evidence was presented to demonstrate that diverse Hsp70 inhibitors—including ATP-competitive agents (VER-155008), allosteric inhibitors (PES), and co-chaperone disruptors (MAL3-101)—effectively de-plete c-FLIP levels. This depletion robustly re-sensitizes resistant cancer cells to apoptosis, which is induced by tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) and Fas ligand (FasL). This overcomes conventional chemoresistance and potentially restores immune-mediated cytotoxicity by dismantling a key protective mechanism. This article details the molecular mechanisms of the Hsp70-c-FLIP axis, evaluates the current landscape of Hsp70-targeted therapeutics, and discusses the significant promise and chal-lenges—such as isoform selectivity and drug development hurdles—of ex-ploiting this chaperone-client relationship. The present review concludes that targeting Hsp70 to disrupt c-FLIP stability represents a highly promising and indirect anticancer strategy, warranting extensive further investigation in both preclinical models and clinical settings.